Determinación de los costos del uso de nematicidas en el cultivo de banano en la hacienda Adriana Carolina, del cantón Valencia, provincia de Los Ríos - Cedeño Franco, Macario José (2017)
Taking into account the low productivity due to the high nematode population index affecting banana production, the identification of nematicide costs is sought as an alternative to improve yield and productivity of banana cultivation. The present research has as main objective the evaluation of three nematicides: one of Carbonates type and two Phosphorous Organ, for which the following specific objectives were established: to evaluate the population level of nematodes by treatment in the application of nematicides in the cultivation of Banana, to establish the productivity response of the banana crop to the application of the nematicides and to perform the economic analysis of the treatments in relation to yield level. The study was carried out at Hacienda Bananera "Adriana Carolina" Canton Valencia, Province of Los Ríos, which is dedicated to the production of bananas of the variety Williams. For the realization of this research a Blocks Full Random design (DBCA) with 4 treatments and 5 repetitions was used. Tukey's Multiple Range Test (p ≤ 0.05) was used to establish the differences between treatment media. Through the analysis of the results it was determined that with the application of Treatment 3 Rugby + Vydate the highest average of Boxes / Ha / Year was reached with 2473.00 and a total cost / ha / year of $ 222.28, differing statistically from The others that reached average values of 2331,80 and 2415,60 Boxes / Ha / Year with a total cost / ha / year of $ 174.31 and $ 195.91 respectively. Keywords: Cost, Nematicide, Profitability, Productivity.